The effect of environment on the fundamental plane of elliptical galaxies. Issue Volume 11:Issue S308(2015) (12th October 2016) - Kipper, R.; Tamm, A.; Tenjes, P.; Tempel, E.
Abstract: We study the effect of environment to fundamental relation of elliptical galaxies. We find that superclusters, filaments and groups give noticeable effect to slope of velocity dispersions while little to luminosity slope.